Effect of different parameters on the serum levels of MDA, NBT, and NO in Andaman local goat breeds - ALYETHODI, RAFEEQUE R; SUNDER, JAI; KARTHIK, S; PERUMAL, P; MUNISWAMY, K; SUJATHA, T; D, BHATTACHARYA (The Indian Journal of Animal Sciences, 2023)
The present study was carried out to assess the effect of rearing systems, breeds, number of pregnancies, and frequency of multiple births on physiological oxidative stress markers (OSMs) in indigenous goat breeds of Andaman and Nicobar Islands, India. Does (n=98) with more than one kidding record maintained in the organized goat breeding farm and at the farmer’s field were selected for the study. Pregnancy records were grouped as more than or less than three pregnancies. Breeds were grouped such as Andaman local goat (ALG) and other indigenous goat breeds. Birth frequency was grouped as single and multiple births. Oxidative stress markers such as malondialdehyde (MDA), superoxide anions, and nitric oxide were analysed in blood serum with respect to the different experimental variables. The free radical superoxide and endogenous nitrite values concerning the breed, multiple birth frequency, number of kidding, and rearing systems were non-significant. Lipid peroxidation through TBARS and nitrate values for the breed, multiple birth frequency, and rearing system were non-significant. However, the pregnancy-wise TBARS and nitrate concentration were significant. Estimates of TBARS were significantly high in the animals with lesser pregnancies (1-3 kidding) while nitrate concentration was significant in higher pregnancies (> 3 kidding). This study revealed that these experimental variables had considerable effects on OSMs in goat breeds under the hot humid tropical island ecosystem of Andaman and Nicobar Islands.